Sustainable vat photopolymerization of complex functional structures with fast dissolvable and recyclable supports - Tengteng Tang; Prem Kalpesh Nawab; Parimal Prabhudesai; Saleh Alfarhan; Ivan Pesqueira; Kalyn VanWormer; Jinxing Li; Dawei Li; Kailong Jin; Xiangjia Li (Virtual and Physical Prototyping)
Vat photopolymerization (VPP)-based 3D printing enables the rapid fabrication of complex, high-precision structures. However, printing intricate features such as overhangs and internal cavities often requires support structures that are difficult to remove and may damage the part surface. To address this, a fast-dissolving, recyclable thiol–ene photopolymer was developed for use as a support material in multi-material VPP printing. The study explores how surface-area-to-volume ratio and grayscale projection influence the dissolution and recyclability of these supports, aiming to minimise post-processing time. Porous gyroid architectures were incorporated into the support structures, achieving dissolution rates up to 50 times faster than solid counterparts. Even after multiple recycling cycles, the thiol–ene resin retains its photopolymerization performance and mechanical properties. This recyclable resin enables the production of intricate geometries – such as microfluidic channels, cactus-inspired spines, and interlocked da Vinci drones – without compromising quality. The results demonstrate that optimally designed porous supports, with high surface-area-to-volume ratios, not only reduce the need for manual post-processing but also enhance sustainability through material reuse. This design approach streamlines the VPP workflow by facilitating faster support removal, reducing cycle times, and lowering both production costs and environmental impact – ultimately enabling more efficient, sustainable, and high-resolution 3D printing.